Carbon Black Tinted Contact Lenses for Reduction of Photophobia in Cystinosis Patients. (4th May 2019) - Dixon, Phillip; Chauhan, Anuj
ABSTRACT: Purpose : To examine if current development on using contact lenses for drug delivery of cysteamine to treat ocular symptoms of cystinosis can be tinted to mitigate photophobia common in patients by reducing transmittance Methods : Commercial contact lenses were placed in a carbon black solution to examine loading after lens synthesis. Silicone hydrogel contact lenses were also synthesized with carbon black added prior to UV curing. Transmittance was measured using UV–vis spectrophotometry over the range of 190–1190 nm and compared to unmodified contact lenses. Lens parameters of refractive index, ion permeability, and Young's modulus were measured using a refractometer, release of sodium chloride, and the cantilever method. Cysteamine release was measured by loading lenses into 5% cysteamine solution and then monitoring the release of the drug using UV–vis spectrophotometry. Vitamin E diffusion barriers were also added to lenses via ethanol solution, and the release of cysteamine from these modified lenses was also examined. Results : No leeching of carbon black was detected during experiments. Loading of pre-made contact lenses led to uneven distribution of carbon black throughout lens. Adding 0.3% carbon black to lens monomer solution prior to UV-curing led to even distribution and a transmittance reduction of approximately 50%. Ion permeability was reduced from 6.19 ± 0.90 x 10 −3 to 1.28 ± 0.06 x 10 −3  mm 2 min −1, and Young's modulus was decreased from 1.58 ± 0.08 to 1.29 ± 0.06 MPa. Cysteamine releases from carbon black lenses with and without vitamin E were comparable to controls, although the loading solution of vitamin E/ethanol had to be tripled to achieve a similar mass loading to control. Conclusions : Carbon black increases the softness of contact lenses, but a loading of 0.3% maintains lens parameters required for wear. The release of cysteamine is also possible with carbon black lenses, albeit requiring a higher loading concentration of vitamin E to achieve similar release times.